Progress in Life Cycle Assessment 2018 - Teuteberg, Frank; Hempel, Maximilian; Schebek, Liselotte (Sustainable Production, Life Cycle Engineering and Management, 2019)
This book comprises recent developments in life cycle assessment (LCA) both with regards to the methodology and its application in various research fields, including mobility, engineering and manufacturing. Containing numerous original research articles from leading German research institutes, the book provides an insightful resource for professionals working in the field of sustainability assessment, for researchers interested in the current state of LCA research as well as for advanced university students in different scientific and engineering fields.